Mechanisms of resistance to chemotherapy in breast cancer and possible targets in drug delivery systems - Lainetti, Patrícia de Faria [UNESP]; Leis-Filho, Antonio Fernando [UNESP]; Laufer-Amorim, Renee [UNESP]; Battazza, Alexandre [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP] (MDPI, 2020)
Breast cancer (BC) is one of the most important cancers worldwide, and usually, chemotherapy can be used in an integrative approach. Usually, chemotherapy treatment is performed in association with surgery, radiation or hormone therapy, providing an increased outcome to patients. However, tumors can develop resistance to different drugs, progressing for a more aggressive phenotype. In this scenario, the use of nanocarriers could help to defeat tumor cell resistance, providing a new therapeutic perspective for patients. Thus, this systematic review aims to bring the molecular mechanisms involved in BC chemoresistance and extract from the previous literature information regarding the use of nanoparticles as potential treatment for chemoresistant breast cancer.
Keywords: Liposomal nanostructures; Neoadjuvant therapy; SiRNA nanoparticles; Treatment resistance